2016
DOI: 10.1021/acs.biochem.6b00338
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Cellular Characterization and Inhibitor Discovery of Pseudomonas aeruginosa 15-Lipoxygenase

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that can cause nosocomial and chronic infections in immunocompromised patients. P. aeruginosa secretes a lipoxygenase, LoxA, but the biological role of this enzyme is currently unknown. LoxA is poorly similar in sequence to both soybean LOX-1 (s15-LOX-1) and human 15-LOX-1 (37 and 39%, respectively) yet has kinetics comparably fast versus those of s15-LOX-1 (at pH 6.5, Kcat = 181 ± 6 s(-1) and Kcat/KM = 16 ± 2 μM(-1) s(-1)). LoxA is capable of efficiently cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Unfortunately, much less is known on the biological relevance of bacterial LOXs but several scenarios have been suggested: (a) Biofilm formation: When planktonic bacteria recognize specific attachment sites, when they suffer from malnutrition or when confronted with sublethal concentrations of antibiotics they form biofilms (Gupta, Sarkar, Das, Bhattacharjee, & Tribedi, ; Hoffman et al, ; Horn & Lackner, ; Karatan & Watnick, ). Recent cell culture experiments suggested that PA‐LOX is required for biofilm formation when P. aeruginosa (PA) interacts with host cells (Deschamps et al, ). The molecular basis for this phenomenon has not been studied in detail but the enzyme might be involved in intercellular lipid signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, much less is known on the biological relevance of bacterial LOXs but several scenarios have been suggested: (a) Biofilm formation: When planktonic bacteria recognize specific attachment sites, when they suffer from malnutrition or when confronted with sublethal concentrations of antibiotics they form biofilms (Gupta, Sarkar, Das, Bhattacharjee, & Tribedi, ; Hoffman et al, ; Horn & Lackner, ; Karatan & Watnick, ). Recent cell culture experiments suggested that PA‐LOX is required for biofilm formation when P. aeruginosa (PA) interacts with host cells (Deschamps et al, ). The molecular basis for this phenomenon has not been studied in detail but the enzyme might be involved in intercellular lipid signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The biological activities of bacterial LOX have not been explored in detail. PA‐LOX has been implicated in pathogen–host interaction (Garreta et al, ) and in biofilm formation (Deschamps et al, ). More recently, the enzyme has been suggested as pathogenicity factor because of its capability of oxidizing membrane lipids of eukaryotic cells (Aldrovandi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…M. tuberculosis can also inhibit the formation of the proinflammatory lipid LTB 4 , further shifting the host lipid environment toward an antiinflammatory state (24). P. aeruginosa produces the 15-lipoxygenase LoxA (25,26), as well as the phospholipase ExoU (27), both of which can potentially generate antiinflammatory signals. However, unlike many airway pathogens, P. aeruginosa survives in a hyperinflammatory environment, particularly in the context of chronic lung disease (2).…”
Section: Discussionmentioning
confidence: 99%
“…LoxA has multiple PUFA substrates and can convert AA and LA to 15S‐hydroxyeicosatetraenoic acid (15S‐HETE) and 13‐HODE. LoxA lacks the leukotriene synthase activity and whether it synthesises lipoxin is still debatable (Banthiya et al, ; Deschamps et al, ; Vance et al, ). The Toxoplasmosis causing parasite Toxoplasma gondii produces the anti‐inflammatory lipoxin LTA 4 and the extracted soluble tachyzoite antigen (STAg) converts AA to 15S‐HETE (Bannenberg et al, ).…”
Section: Microbial Oxylipins: Enzymes and Productsmentioning
confidence: 99%
“…Recombinant P. aeruginosa LoxA modifies membrane phospholipids by forming 15S‐HETE and 13‐HODE, which is associated with induction of red blood cell haemolysis (Banthiya et al, ). LoxA is highly expressed in P. aeruginosa isolated from CF lungs and is implicated in biofilm formation on biotic surfaces, such as epithelium (Deschamps et al, ; Starkey et al, ).…”
Section: Microbial Oxylipins: Effect On Inflammation and Virulencementioning
confidence: 99%